The Role of Laparoscopic Cholecystectomy In Acute Cholecystitis - Sogutlu, Gokhan; Ara, Cengiz; Yilmaz, Sezai; Kirimlioglu, Hale; Karadag, Nese; Keskin, Lezzan (Annals of Medical Research, 2021)
None
Keywords: Acute Cholecystitis, Laparoscopic Cholecystectomy, Conversion